Fortifying student engagement throughout online learning in Entrepreneurship subject during Covid-19 pandemic - Valeny Suryaningsih; Agriqisthi Agriqisthi (Management Institute Faculty of Economics Universitas Andalas, 2021)
Entrepreneurship is important to economic advancement, employment as well as a solution to the excessive number of university graduates and social problems. Even more, it is important to know the factors that influence students’ engagement in entrepreneurship learning. Why so? It will build profound understanding about entrepreneurship, and if it is possible student will do small business simulation to experience their theories to launch new start-up business. Moreover, due to special circumstances happened nowadays, Covid-19 pandemic need special treatment to keep student vibrant and captivating about their study. Online classes acquire smart and efficient strategies to provide effective learning experiences to the students. The study that conducted by Suryaningsih (2021) had discovered by providing group discussion session, lecturer has generated enthusiasm for learning and student’s interaction during online learning. The grounded questions are about how lecturers generate students’ enthusiasm and interaction during online learning entrepreneur subject, how student fortify their soft skill along online learning entrepreneurship subject and how about the satisfaction and competencies of students by engaging the class of entrepreneurship subject. This study is quantitative descriptive research. It is applied through questionnaire by having open and close question. The result of this study, lecturers generate students’ enthusiasm and interaction during online learning entrepreneurship subject in many ways. The most way that lecturer utilized is giving the interactive learning method example by utilizing youtube, video, etc). Student fortify their soft skill along online learning entrepreneurship subject by fulfilling the assignment and being active in FGD and class discussion. After taking the Entrepreneurship subject online learning, students could optimally train their soft skill in the class and their soft skill increases. Therefore, students recommend the learning strategy in this class to be adopted by other Entrepreneurship’s classes.